Pengaruh Terpaan Konten Instagram Paragonation Terhadap Citra PT Paragon Technology and Innovation (Survei pada Followers Akun Instagram @Paragonation) - Nur Hamidah; Istisari Bulan Lageni (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the influence of exposure to @paragonation Instagram content on the image of PT Paragon Technology and Innovation among followers of the @paragonation Instagram account in the context of corporate digital communication. The study employs a quantitative approach with an explanatory survey design, utilizing an online questionnaire distributed to followers who had viewed the “Paragon Flies an Airplane” Reels content. Data were analyzed using SPSS version 31.0 through descriptive tests, simple linear regression, t-tests, and the coefficient of determination. The results indicate that Instagram content exposure falls into the high category, dominated by the attention dimension, while the company’s image received very positive ratings in the dimensions of corporate personality, corporate reputation, corporate value, and corporate identity. Statistical analysis revealed a significant influence of Instagram content exposure on corporate image, with a coefficient of determination of 53.8%. These findings demonstrate that Instagram Reels can function as an effective digital public relations tool in building positive perceptions, social legitimacy, and emotional closeness between companies and the public in the era of interactive social media.